Perceived stress in addicted individuals in treatment by the Cohen scale: psychometric properties and results of its application - Pedrero Pérez, Eduardo J.; Olivar Arroyo, Álvaro (Anales de Psicología / Annals of Psychology, 2010)
Stress is strongly related to addiction throughout all its stages. Since Lazarus published his theoretical framework, stress is considered a product of the individual’s evaluation of threats and the available re-sources to face them. Perceived Stress Scale (PSS) is a widely used test in research and clinics, although it has not been usually applied in addicted individuals. In a sample of 133 individuals in treatment of addictive behav-iors, PSS and MCMI-II were used. Psychometric properties of the ques-tionnaire were studied in this sample, resulting adequate. High levels of perceived stress were found in individuals at the beginning of treatment, being lower in individuals who were abstinent for more than three months. Average levels were also lower than those found in individuals suffering from major depression. On the other hand, they resulted to be higher than those obtained from most of the non-clinic population who answered this test in previous works. Results in PSS, in all three different versions, were highly correlated with Axis I and II disorders, as measured with the MCMI-II. The study and evaluation of subjective stress may be necessary to adequately elucidate the psychological disorders associated with addiction.